Application of Advanced Encryption Standard (AES) Algorithm in E-Commerce Login System for User Data Security - Ifani, Aulyah Zakilah; S.Intam, Rezki Nurul Jariah; Syair, Andi Irfandi; Husnawati, Husnawati (Universitas Pancasakti, 2025)
E-commerce becomes an electronic media that uses a login system used by users. User data in the form of usernames and passwords is vulnerable to hacking. One technique to improve user security is the implementation of AES algorithms on login systems in E-Commerce applications. The purpose of this study is to apply the AES algorithm in the login system of e-commerce websites and analyze the improvement of information security for users after the implementation is carried out. The research method used is an experiment with the application of the use of the AES algorithm before and after. Therefore, the application of the AES algorithm on the login system of e-commerce websites can be used as a solution to improve user data security. Testing using Wireshark and Burpsuite tools. The results obtained are that AES successfully secures the username and password on the e-commerce login system .